Menggay's magical chicken Ang mahiwagang manok ni Menggay - Alfar, Nikki (Lampara books, 2012)
"Menggay has an unusual pet chicken. The chicken can do magic. it makes patterns of grains on the ground that contain important messages for Menggay to read. That is why Menggay can tell when it is going to rain, what made the neighbor's carabao sick, and how the albularya lost her gold ring. One day, Menggay magical chicken is stolen by a blue-eyed, bluish-skinned man. Find out in this story how Menggay goes about looking for her chicken--and how moral values that should be learned early in childhood can help a lot."